2014
DOI: 10.4238/2014.august.25.9
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the expression of integrin β1, VEGF and MVD in hypopharyngeal squamous cell carcinoma

Abstract: ABSTRACT. This study aimed to determine the expression of integrin β1 and vascular endothelial growth factor (VEGF) and microvascular density (MVD) by CD105 staining in hypopharyngeal squamous cell carcinoma to determine their association with clinicopathologic characteristics, and to determine their role and the effects of their interactions in the development and progression of hypopharyngeal squamous cell carcinomas. The expression of integrin β1 and VEGF and MVD in hypopharyngeal squamous cell carcinomas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
3
Order By: Relevance
“…Similar to the controversy concerning metastasis, the associations between β1 integrin and the clinical features of patients are unclear. In certain types of cancer, β1 integrin is associated with poor prognosis or metastasis, including in prostatic cancer (15,24), melanoma (25), gastric carcinoma (26) and hypopharyngeal squamous cell carcinoma (27). However, in other types of cancer, including breast cancer, studies have reported different or contradictory conclusions (28)(29)(30).…”
Section: Metastasismentioning
confidence: 97%
“…Similar to the controversy concerning metastasis, the associations between β1 integrin and the clinical features of patients are unclear. In certain types of cancer, β1 integrin is associated with poor prognosis or metastasis, including in prostatic cancer (15,24), melanoma (25), gastric carcinoma (26) and hypopharyngeal squamous cell carcinoma (27). However, in other types of cancer, including breast cancer, studies have reported different or contradictory conclusions (28)(29)(30).…”
Section: Metastasismentioning
confidence: 97%
“…These facts suggest that targeting integrins overexpressed in cancer cells is a feasible strategy for use in cancer nanomedicine. Fibronectin Increases tumor progression [38] Increases cancer invasion [39] Mediates resistance to radiotherapy [36] Head and neck cancer [40,41] Vitronectin Non-small cell lung cancer [42] Fibrinogen Breast cancer [43] Osteopontin Prostate cancer [44] Ovarian cancer [45] Melanoma [46] ανβ3…”
Section: Integrins In Cancer Nanomedicinementioning
confidence: 99%
“…Множество проведенных исследований по изучению зако-номерностей роста и прогрессии опухолей кожи показа-ли, что чем выше содержание интегринов в опухоли, тем выше скорость ее инвазии и более выраженный ангиогенез [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Суть этих исследований заключалась в сравнении количества интегринов на разных клонах одной и той же опухоли, с определением скорости роста, инвазии и мета-стазирования каждого из клонов с последующим сравне-нием их между собой.…”
Section: влияние интегринов на прогрессию опухолей кожиunclassified
“…Суть этих исследований заключалась в сравнении количества интегринов на разных клонах одной и той же опухоли, с определением скорости роста, инвазии и мета-стазирования каждого из клонов с последующим сравне-нием их между собой. Результаты всех исследований были схожими: клоны, имевшие самый быстрый и злокаче-ственный рост, показывали наибольшую экспрессию ин-тегринов по сравнению с менее агрессивными вариантами тех же опухолей [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: влияние интегринов на прогрессию опухолей кожиunclassified
See 1 more Smart Citation